The influence of vegan diet on bone mineral density and biochemical bone turnover markers - Jadwiga Ambroszkiewicz; Teresa Laskowska-Klita; Edward Franek; Magdalena Chełchowska; Joanna Gajewska; Witold Klemarczyk (Pediatric Endocrinology, Diabetes and Metabolism)
Introduction: Vegetarian diets can be healthy when they are well balanced and if a variety of foods is consumed. However, elimination of animal products from the diet (vegan diets) decreases the intake of some essential nutrients and may influence the bone metabolism. This is especially important in childhood and adolescence, when growth and bone turnover are most intensive. The aim of the study was to assess the effect of vegan diet on bone density (BMD) density and serum concentrations of bone metabolism markers. Material and methods: We examined a family on vegan diet which consisted of parents and two children. Dietary constituents were analysed using a nutritional program. Total and regional BMD were measured by dual-energy X-ray absorptiometry. Concentrations of calcium and phosphate in serum obtained from fasting patients were determined by colorimetric methods, 25-hydroxyvitamin D by the chemiluminescence method and bone turnover markers by specific enzyme immunoassays. Results: In studied vegans, the dietary intake of phosphate was adequate while calcium and vitamin D were below the recommended range. Concentrations of calcium, phosphate and bone turnover markers in the serum of all subjects were within the physiological range, but 25-hydroxyvitamin D level was low. Age-matched Z-score total BMD was between -0.6 and 0.3 in adults, however in children it was lower (-0.9 and -1.0). Z-score BMD lumbar spine (L2-L4) was between -0.9 to -1.9 in parents and -1.5 to -1.7 in children. Conclusions: Our results suggest that an inadequate dietary intake of calcium and vitamin D may impair the bone turnover rate and cause a decrease in bone mineral density in vegans. The parameters of bone density and bone metabolism should be monitored in vegans, especially children, in order to prevent bone abnormalities.